The Employee Performance Evaluation by using the Hybrid Multi-Criteria Decision-Making Approach - Rizana, Afrin Fauzya; Kurniawati, Firdah Dipi Juni; Rumanti, Augustina Asih (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study is aimed to develop a multi-criteria decision-making model for evaluating employee performance and provide organizations with a guideline on how to quantify employee performance.Methodology: A hybrid approach of AHP and WSM was used in the development of the employee performance model. The AHP approach was employed to obtain the weight of each criterion. The obtained weight value is then used to calculate the performance score.Finding: Based on the literature review and interviews, nine criteria were used, namely the achievement of work targets, job knowledge, initiative, work discipline, responsibility, teamwork, integrity, communication, and cleanliness. Based on weight calculations, it was found that achievement of the work target has the highest importance weight, followed by job knowledge, initiative, work discipline, responsibility, teamwork, integrity, communication, and cleanliness.Conclusion: This study developed a multi-criteria decision-making model and a scoring guideline for evaluating employee performance. According to the results of the performance score, the assessed employee would fall into five categories i.e. unacceptable performance, performance is slightly under the minimum expectation, performance meets the standard and expectation, performance exceeds the standard and expectation, and extraordinary performance. The model can be used to help managers to make decisions regarding compensation which is to be given to employees by linking the employee performance category with compensation criteria.